Development in Africa : refocusing the lens after the millennium development goals - Kararach, George; Besada, Hany; Shaw, Timothy (Policy Press, 2015)
In this important work the contributors argue that Africa as a continent must work on securing social and political stability and building effective economic governance to ensure the development of a society that is socially, economically and politically inclusive.